The phenomena of electron charge ejection during the hot electron beam transportation - Tarasov, I.K.; Sytnykov, D.A.; Tarasov, M.I. (Вопросы атомной науки и техники, 2006)
The transportation of hot electron beam through the drift chamber along the magnetic field was experimentally studied. The main attention was paid to the phenomena of electron charge ejection on the drift chamber wall. Experimental results shows that self-consistent Penning-Malmberg trap occurs after the stage of non-stationary virtual cathode with the limiting of electrons current in axial direction and radial ejection of electrons on the chamber wall.